KAJIAN PENGGUNAAN KULIT BUAH MELINJO (Gnetum gnemon) SEBAGAI SUMBER ENZIM PROTEASE - R. A. Sidqi Zaed Z.M. (Agrovigor, 2010)
The research consist of six parts.  These studies aim at : (1) seeking an accurate of extraction–isolation methode in peel of Gnetum gnemon, (2) determining pH optimum enzyme protease in peel of Gnetum gnemon, (3) determining the optimum temperature of enzyme protease in peel of Gnetum gnemon, (4) knowing the activity of enzyme in several concentrations, (5) knowing kind of enzyme based on its active, and (6) knowing the stability of enzyme to high temperature in peel of Gnetum gnemon.The research was done on February to September 2008  at Base Laboratory  of Trunojoyo University and Biochemestry Laboratory of Brawijaya University.  The first research uses saturate sulate ammonium 50 % and 60 %, acetone 1:1 and ethanol 1:1.  Observation was done on enzyme activities resulted (µmol tir.ml-1.min-1) and its rendement (%).  Extraction methode by ammonium sulfate 60 % µmol tir.ml-1.min-1 is the best methode with activity 62.15 x 10- 2   µmol tir.ml-1.min-1 and yields 1.52 %.The second research was examined in pH 4.0, 4.5, 5.0, 6.0, 7.0, 7.5, 8.0 and 8.5.  The research result shows that the optimum activity of enzyme protease in peel of Gnetum gnemon around pH neutral is 6.5 (60.33 x10- 2   µmol tir.ml-1.min-1).The third research was experimented on temperature 30, 35, 40, 45, 50, 60, 65 and 70 degrees Celsius.  The research result shows that enzyme protease which extracted in peel of Gnetum gnemon  indicates the highiet activity 40 degrees Celcius with activity 63.94 x 10- 2   µmol tir.ml-1.min-1. The fourth research uses substrate casein 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4 and 1.6 % (b/v).  The research concludes that concentration of substrate casein 0.8 % shows a saturate.  The highest activity value is 63.49 x 10- 2   µmol tir.ml-1.min-1. The fifth research shows that the highest enzyme activity becaused of the influences HCN (64.26 x    10- 2   µmol tir.ml-1.min-1.  Therefore, it can be concluded that enzyme protease in peel of Gnetum gnemon is sulfidril (sulfide).The sixth research shows that the stability endures until 50 degrees Celcius (59.84 x 10- 2   µmol tir.ml-1.min-1.  It means that enzyme protease in peel of Gnetum gnemon is kind of enzyme protease with high temperature stability.